Estetika dan Kesehatan Gigi Sebagai Determinan Self Esteem pada Remaja Putri di Sekolah Menengah Atas - Ulfah, Aulia; Zahara, Meutia; Marthoenis, M.; Baharuddin, Dharina; Aramico, Basri (FORIKES, 2025)
Oral health problems remain a challenge in various countries, including Indonesia, with a relatively high prevalence of malocclusion. This condition not only impacts oral function but also causes psychosocial effects, especially in adolescents who are very concerned about dental appearance and aesthetics. The purpose of this study was to analyze the relationship between dental aesthetics and self-esteem in adolescents. The study used a cross-sectional design involving 180 female students aged 15–17 years selected through a total sampling method. Data were collected through intraoral examinations using the Index of Orthodontic Treatment Need (IOTN) which includes the Aesthetic Component (AC) and Dental Health Component (DHC), as well as the Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ) questionnaire to assess self-esteem. Data analysis was performed using simple and multiple linear regression tests. The results showed that the statistical values for AC were B = -0.443, p = 0.000, and β = -0.24; Meanwhile, for DHC, B = -1.797, p = 0.000, and β = -0.48, indicating that dental aesthetics is significantly related to self-esteem, with DHC having the strongest influence on decreasing self-esteem. Meanwhile, difficulty chewing and speaking, as well as dental visits, did not show a significant relationship with self-esteem. These findings conclude that dental aesthetics is a determinant of adolescent self-esteem, thus requiring attention in efforts to improve their quality of life.Keywords: dental aesthetics; aesthetic component; dental health component; malocclusion severity; self-esteem ABSTRAK Masalah kesehatan gigi dan mulut masih menjadi tantangan di berbagai negara, termasuk Indonesia, dengan prevalensi maloklusi yang cukup tinggi. Kondisi ini tidak hanya berdampak pada fungsi oral, tetapi juga menimbulkan efek psikososial, terutama pada remaja yang sangat memperhatikan penampilan dan estetika gigi. Tujuan penelitian ini adalah menganalisis hubungan antara estetika gigi dengan self-esteem pada remaja. Penelitian menggunakan desain cross-sectional dengan melibatkan 180 siswi berusia 15–17 tahun yang dipilih melalui metode total sampling. Data dikumpulkan melalui pemeriksaan intraoral menggunakan Index of Orthodontic Treatment Need (IOTN) yang mencakup Aesthetic Component (AC) dan Dental Health Component (DHC), serta kuesioner Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ) untuk menilai self-esteem. Analisis data dilakukan dengan uji regresi linier sederhana dan berganda. Hasil penelitian menunjukkan bahwa nilai statistik untuk AC adalah B = -0,443, p = 0,000, dan β = -0,24; sementara itu untuk DHC adalah B = -1,797, p = 0,000, dan β = -0,48, yang menunjukkan bahwa esttika gigi berhubungan secara signifikan dengan self-esteem, di mana DHC memberikan pengaruh paling kuat terhadap penurunan self-esteem. Sementara itu, kesulitan mengunyah dan berbicara serta kunjungan ke dokter gigi tidak menunjukkan hubungan yang bermakna edngan self esteem. Temuan ini menyimpulkan bahwa estetika gigi merupakan determinan self-esteem remaja, sehingga perlu menjadi perhatian dalam upaya peningkatan kualitas hidup mereka.Kata kunci: estetika gigi; aesthetic component; dental health component; keparahan maloklusi; self esteem